1999
DOI: 10.1007/s004280050338
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous occurrence of Hodgkin's disease, nodal Langerhans' cell histiocytosis and multiple myeloma IgA(κ)

Abstract: A 35-year-old man suffered simultaneously from nodular sclerosis Hodgkin's disease (HD), Langerhans' cell histiocytosis and multiple myeloma (MM). There was no prior history of irradiation or chemotherapy, and clinically the lymphoma was confined to cervical lymph nodes. Immunohistochemically, neoplastic lymphoma cells reacted with CD15 and CD30 markers. The patient's bone marrow exhibited a diffuse infiltration by rather atypical plasma cells showing kappa immunoglobulin light-chain restriction. At 14 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…Those HRS cells that continue to express SDC1 are perhaps more aggressive than their SDC1 negative counterparts, thus contributing to the aggressive nature of poor outcome cHL, and producing the sort of unfavorable prognosis that is typical of primary refractory and early relapsing cHL patients. Of additional interest is the coexistence of HRS cells with aggressive multiple myeloma [65], or their appearance after treatment of multiple myeloma [66]. …”
Section: Discussionmentioning
confidence: 99%
“…Those HRS cells that continue to express SDC1 are perhaps more aggressive than their SDC1 negative counterparts, thus contributing to the aggressive nature of poor outcome cHL, and producing the sort of unfavorable prognosis that is typical of primary refractory and early relapsing cHL patients. Of additional interest is the coexistence of HRS cells with aggressive multiple myeloma [65], or their appearance after treatment of multiple myeloma [66]. …”
Section: Discussionmentioning
confidence: 99%
“…Analyses of lymphomas with an excess of LC are few in as [8][9][10][11][12] with an occasional series of four or six patients and review of the literature [3,4]. Our series, the largest to be reported, studies many clinical and pathological issues and provides analysis of the significance of this association.…”
Section: Discussionmentioning
confidence: 85%
“…One case of developing HD after LCH has also been reported [6]. Ibarrola de Andres C. et al reported simultaneous occurrence of Hodgkin's disease, Langerhans cell histiocytosis and multiple myeloma in a 35-year-old man [7] while Karadeniz G. et al reported the simultaneous development of HD and LCH in a 6-year-old boy [8] and Kjeldsberg C. R. et al described the combination of eosinophilic granuloma and malignant lymphoma in the same lymph node [5]. …”
Section: Discussionmentioning
confidence: 99%